Joint use of microwave and glycerol-zinc (II) acetate catalytic system in the synthesis of 2-pyridyl-2-oxazolines - Carmona Rafaela C.; Schevciw Evelyn P.; de Albuquerque João L. Petrarca; Wendler Edison P.; Dos Santos Alcindo A. (Green Processing and Synthesis, 2013)
Glycerol combined with zinc (II) acetate catalyzed the reaction of 2-amino alcohols and 2-cyanopyridines under microwave irradiation, resulting in 2-pyridyl-2-oxazolines. Comparing the conversion to that obtained by conventional heating, a significant decrease in the reaction time was achieved. At the end of the reaction, the product was isolated and the glycerol-zinc (II) acetate catalytic system was recycled four times for the same transformation in reasonable to acceptable yields. The products were obtained in their pure form by simple filtration in a short pad of silica.